A neural network based ionospheric model over Africa from Constellation Observing System for meteorology, ionosphere, and climate and ground Global Positioning System observations - Okoh, Daniel; Seemala, Gopi; Rabiu, Babatunde; Habarulema, John Bosco; Jin, Shuanggen; Shiokawa, Kazuo; Otsuka, Yuichi; Aggarwal, Malini; Uwamahoro, Jean; Mungufeni, Patrick; Segun, Bolaji; Obafaye, Aderonke; et al. (My University, 2019)
The first regional total electron content (TEC) model over the entire African region (known as AfriTEC model) using empirical observations is developed and presented. Artificial neural networks were used to train TEC observations obtained from Global Positioning System receivers, both on ground and onboard the Constellation Observing System for Meteorology, Ionosphere, and Climate satellites for the African region from years 2000 to 2017. The neural network training was implemented using inputs that enabled the networks to learn diurnal variations, seasonal variations, spatial variations, and variations that are connected with the level of solar activity, for quiet geomagnetic conditions (âˆ’20 nT â‰¤ Dst â‰¤ 20 nT). The effectiveness of three solar activity indices (sunspot number, solar radio flux at 10.7â€ cm wavelength [F10.7], and solar ultraviolet [UV] flux at 1 AU) for the neural network trainings was tested. The F10.7 and UV were more effective, and the F10.7 was used as it gave the least errors on the validation data set used. Equatorial anomaly simulations show a reduced occurrence during the June solstice season. The distance of separation between the anomaly crests is typically in the range from about 11.5 Â± 1.0Â° to 16.0 Â± 1.0Â°. The separation is observed to widen as solar activity levels increase. During the December solstice, the anomaly region shifts southwards of the equinox locations; in year 2012, the trough shifted by about 1.5Â° and the southern crest shifted by over 2.5Â°.
Keywords: Climate; Global positioning system; Ionosphere; Meterology; Neural Network Based Ionospheric Model; Global Positioning System